Comparison of various methods of fetal weight estimation at term pregnancy - Rani, Sangeeta; AnmolPreet kaur; Parneet Kaur; Navkiran Kaur (GMC Patiala Journal of Research and Medical Education, 2023)
Introduction: Various factors have been noted which can affect fetal and neonatal morbidity and survival. However, it has been seen that amongst them the birth weight is the mostimportant variable that affects it.Therefore estimation of fetal weight is very crucial in management of labor and delivery. The most-commonly used methods for estimating fetal weight are clinical and ultrasonographic methods, with each one having its limitations. Our aim of this study was to compare the fetal weight estimation with both these methods at term pregnancy and to compare them to the actual birth weight of the baby. Materials and methods:A prospective comparative study covering 100 women at term pregnancy with a single fetus in cephalic presentation was conducted in Department of Obstetrics and Gynaecology, Government Medical College, Patiala. Fetal weight was estimated by Johnson's, Dare's and Hadlock's methods. Fetal weight taken by each method was compared to actual birth weight of the newborn. Results were compiled and analyzed statistically. Results: The estimated fetal weight calculated by Hadlock’s formula and actual birth weight (p=0.83) had no significant difference as compared to the Dare’s formula (p=0.008) and Johnson’s formula (p<0.001). The average error<10% shown was 65% cases with Dare’s formula, 35 % cases with Johnson’s formula and 77% cases with Hadlock’s formula. The least average error was with Hadlock’s. Conclusion:Hadlock’s formula found to be with superior results and has better predictable results in fetal weight estimation, compared to other two formulae, but when facilities for ultrasound are not available readily, like in developing countries, clinical estimation by Dare’s formula is a better option than Johnson’s formula.